Implementasi Merdeka Belajar terhadap Kesulitan Belajar Anak Disleksia ( SDN Pacarkeling 5 Surabaya ) dengan Pendampingan Khusus - Kurnia Sri Dewi; Rizkya Dwijayanti; Isrida Yul Arifiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Freedom of Learning is one of the new policies in the world of education that has been issued by the Ministry of Education and Culture which is implemented for college students and students. This policy is carried out as a transformation in success in the academic field. Learning difficulties that afflict dyslexic students make educators feel less able to maximize their teaching, so that not a few dyslexic students are always neglected or left behind in classroom learning. Because of this new policy that makes inclusive children allowed to go to public schools, but many public schools actually cannot accept their arrival because of the lack of knowledge or how to understand dyslexic children's learning by educators. So that special assistance is one solution for schools so that the knowledge and interest of dyslexic children continues to increase.